Teknik Relaksasi Butterfly Hug Terhadap Penurunan Kecemasan Siswa SMA Negeri 1 Natar - Triyoso Triyoso; Muhammad Syamsul Muarif; Maida Saputri; Putri Indaman; Mia Nurar Lina; Hilda Meilinda; Mutiara Natalia; Ray Krisna Dhitya (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Anxiety is a vague, pervasive feeling of anxiety accompanied by feelings of worry and helplessness. This emotional state has no specific object and is experienced subjectively. Anxiety can cause decreased self-confidence, poor academic performance, problems with friends, and other conflicts. Fear that lasts a long time and continues to increase can trigger anxiety disorders. The butterfly hug technique is a therapy developed by psychologists to reduce anxiety. The aim of this activity is to increase knowledge about the butterfly hug relaxation technique to reduce anxiety in students. The results of the Self Reporting Questionnaire (SRQ) 20 questionnaire from this community service activity were that out of 36 students, there were 7 students who needed the nearest health worker to consult because they answered "YES" to more than 6 questions. Apart from that, all respondents (100%) were able to follow the butterfly hug relaxation technique which was demonstrated very well. Students are expected to more easily overcome the fears they face and improve the quality of their learning experience